Tinjauan Maqasid Al-Syariah Terhadap Pola Integrasi Zakat, Wakaf, dan Social Finance di Era Digital: A Review of Maqasid Al-Syariah on The Integration of Zakat, Wakaf, and Social Finance in The Digital Age - Zaenudin, Zaenudin (ISTIDLAL, 2025)
Zakat and wakaf hold great potential as instruments of wealth redistribution and social financing; however, their management remains fragmented and suboptimal, particularly in the digital era. This study aims to explain the relevance of maqasid al-sharī‘ah as a legal framework for ijtihād in developing Islamic social finance in the digital context and to formulate a maqasid-based integrative model of zakat–wakaf–social finance for sustainable poverty alleviation. The research applies a normative legal method using conceptual and maqasidi approaches, analyzing primary and secondary sources related to Islamic economic law, zakat–wakaf regulation, and sharia-compliant digital finance innovation. The findings indicate that maqasid al-sharī‘ah provides both normative and methodological foundations for integrating digital Islamic social finance through the principles of maṣlaḥah, justice, and transparency. The study proposes the Maqasid-Based Integrated Social Finance Framework, which positions zakat as a liquidity layer, wakaf as a sustainability layer, and digital social finance as an acceleration layer. This model offers an innovative and inclusive policy framework for Islamic economic law that promotes social justice and economic empowerment in the digital era.